IMF Survey, Volume 31, Issue 17. (IMF Survey; IMF Survey ;, 2002)
The world's finance ministers and central bank governors will gather in Washington on September 29 for the Annual Meetings of the Governors of the IMF and the World Bank, against a backdrop of increased concerns about the strength and durability of the global economic recovery. On September 28, the International Monetary and Financial Committee (IMFC), the IMF's principal advisory Committee of Governors, and the Development Committee, a joint committee of IMF and World Bank Governors, will meet. The Annual Meetings have been shortened, owing to U.S. security concerns.